Matin Luther’s view on Visual Arts and Sinicization - CHEN, Qirui (Journal of Research for Christianity in China (JRCC), 2025)
Martin Luther (1483-1546) never uses the term “visual arts”, which, remains indispensable for his theological articulation and practice. Since 1522, the Iconoclsam under the Spiritualists had caused social turbulence in Wittenberg and the other places in Europe. Luther set forth his view on visual arts defending against that radical deed. Through the Biblical interpretations and theological treatises, Luther had made the social situation stable successfully. In Luther’s discussion from 1522 to 1545, we find his dialectical, Biblical and theological attitude and position on visual arts. For Luther, visual arts could be used in church life as far as they were regarded as a way of understanding belief, rather than al. According to Luther’s view on visual arts, this paper displays the analysis of his historical backdrop, theological foundation and some assessment, as well as applies Luther’s on visual arts into the modern context in China. In doing so, it demonstrates that Martin Luther’s idea of visual arts can be utilized for the exploration of Christian Sinicization today.